Hypoxia Tolerance in Teleosts: Implications of Cardiac Nitrosative Signals - Gattuso, Alfonsina; Garofalo, Filippo; Cerra, Maria C.; Imbrogno, Sandra (Frontiers in Physiology, 2018)
Changes in environmental oxygen (O2) are naturally occurring phenomena which ectotherms have to face on. Many species exhibit a striking capacity to survive and remain active for long periods under hypoxia, even tolerating anoxia. Some fundamental adaptations contribute to this capacity: metabolic suppression, tolerance of pH and ionic unbalance, avoidance and/or repair of free-radical-induced cell injury during reoxygenation. A remarkable feature of these species is their ability to preserve a normal cardiovascular performance during hypoxia/anoxia to match peripheral (tissue pO2) requirements. In this review, we will refer to paradigms of hypoxia- and anoxia-tolerant teleost fish to illustrate cardiac physiological strategies that, by involving nitric oxide and its metabolites, play a critical role in the adaptive responses to O2 limitation. The information here reported may contribute to clarify the molecular and cellular mechanisms underlying heart vulnerability vs resistance in relation to O2 availability.